2002
DOI: 10.1021/jf011128i
|View full text |Cite
|
Sign up to set email alerts
|

Coriander Essential Oil Composition from Two Genotypes Grown in Different Environmental Conditions

Abstract: The objective was to study the essential oil composition of coriander fruits in plants growing in environments differing in soil conditions and weediness level. Factorial field experiments were conducted in two locations from the Rolling Pampas, Argentina, and two coriander landraces (European and Argentinean) were tested under two levels of nitrogen fertilization and weediness. Data were evaluated with uni- and multivariate techniques. The variation in the oil composition was related to the relative proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
76
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 28 publications
11
76
2
2
Order By: Relevance
“…In the present study, according to GC-FIS and GC-MS analyses of CEO, we identified that the major component was the monoterpene linalool (81.7%), addition to various constituents in minor quantity as g-terpinene, a-pinene and camphor (3-6%), among others. These results were consistent with similar values reported by Gil et al (2002) for CEO obtained from seeds of varieties grown in our country. The yield of coriander seed essential oil obtained by hydrodistillation is 0.1-5.2% being mostly linalool (65-83%).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, according to GC-FIS and GC-MS analyses of CEO, we identified that the major component was the monoterpene linalool (81.7%), addition to various constituents in minor quantity as g-terpinene, a-pinene and camphor (3-6%), among others. These results were consistent with similar values reported by Gil et al (2002) for CEO obtained from seeds of varieties grown in our country. The yield of coriander seed essential oil obtained by hydrodistillation is 0.1-5.2% being mostly linalool (65-83%).…”
Section: Discussionsupporting
confidence: 93%
“…The predominant compounds detected in this study agree with those reported by other researchers for coriander essential oil (Purseglove et al 1981;Formáček and Kubeczka 1982;Kerrola and Kallio 1993;Frank et al 1995;Diederichsen 1996;Jeliazkova et al 1997;Bandoni et al 1998;Baratta et al 1998;Misharina 2001; Fig. 2 Phenetic relationships among 60 coriander populations based on the first three principal components from phenotypic data, presented as a three-dimensional scatter plot Table 6 Comparison of 60 coriander accessions from NCRPIS, with infraspecific taxa, as proposed by Diederichsen and Hammer (2003) Smallfield et al 2001;Gil et al 2002). In addition, mean percentages for compounds, based on their presence in essential oil samples (Table 7), generally agree with earlier reports; Diederichsen and Hammer (2003) highlighted linalool, camphor, limonene, and myrcene as very useful compounds for infraspecific classification in coriander.…”
Section: Identification Of Seed Essential-oil Componentssupporting
confidence: 88%
“…The essential oil quality and productivity of dill and other essential oil crops depend on many factors such as climate, cultivar, seeding date, harvest date, weed pressure, plant disease, and management practices (Frank et al 1987;Kothari et al 1989;Zheljazkov and Zhalnov 1995;Rangappa et al 1997;Gil et al 2002). Dill has been grown throughout the world as an essential-oil-producing crop with a large portion of the industry centered in Europe.…”
mentioning
confidence: 99%